The Effect of Learning Orientation on Business Performance Through Mediation of Innovation Dimensions in UMKM in Mataram City Indonesia - I Made Suardana; Ni Nyoman Yuliati; Agus Khazin Fauzi; I Nengah Arsana; Baiq Desthania Prathama (Optima Science, 2024)
This research is directed to build a model that can provide predictions of the influence of learning orientation (X1) on the dimensions of innovation (product innovation/Y1; process innovation/Y2; marketing innovation/Y3 and organizational innovation/Y4) as well as the influence of each dimension of innovation on business performance (Z1) of small businesses in Mataram City. Observation data in this study were 78 small business actors, with the criteria of having run their business for at least three years. The analysis tool uses PLS (partial least square) analysis. According to the PLS work procedure, there are two stages of model formation, because the initial model still has indicators with a correlation value of less than 0.70, namely indicators X1.1 and Z1.1. The second model has met the indicator validity and reliability requirements, so there is no indicator removal process. The final model produced meets the predictive relevance requirements (Q2>0). All dimensions of innovation are positively and significantly influenced by learning orientation, but only two dimensions of innovation (product innovation and process innovation) have a positive and significant effect on the business performance of small businesses in Mataram City. This gives an indication of learning orientation as an absolute by the company owner to be made a culture in the organization and should be focused on product aspects and the application of appropriate technology.